Effect of Financial Literacy and Access to Capital on the Growth of Micro, Small, and Medium Enterprises - Mohammad Rizky Yahya; Ratih Puspitasari; Irmah Halimah Bachtiar; Samalua Waoma; Victor Pattiasina (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
This study aims to determine and analyze effect of financial literacy and access to capital on the growth of Micro, Small, and Medium Enterprises. This study applies a quantitative research design. Population in this research is Micro, Small, and Medium Enterprises in Medan City. Sampling technique used purposive sampling with a sample of 50 respondents from Micro, Small, and Medium Enterprises in Medan City. Testing the hypothesis in this study using multiple linear regression. The results show that financial literacy has a positive and significant effect on the growth of Micro, Small, and Medium Enterprises. Access to capital has a positive and significant effect on the growth of Micro, Small, and Medium Enterprises.